PERSEPSI MAHASISWA DKV FSD UNM TERHADAP DESAIN GRAFIS LINGKUNGAN DAN DESAIN INFORMASI BERTEMA LINGKUNGAN HIDUP - Nurabdiansyah, Nurabdiansyah; Mandra, Moh. Ahsan S. (UNM Environmental Journals, 2023)
Environmental Graphic Design (EGD) is a design discipline concerned with the creation and arrangement of graphic design elements in a physical environment. While environment-themed information design refers to the use of graphic design to convey messages about environmental issues. Environmental Graphic Design in this context is a medium of conveying messages through visual communication design. This study analyzes the perception of students of the Visual Communication Design (DKV) department, Faculty of Art and Design, Universitas Negeri Makassar (UNM) towards Environmental Graphic Design and environment-themed information design. The research was conducted by asking simple questions about Environmental Graphic Design and environment-themed information design. It was concluded that students know the use of graphic design and information design to convey messages about environmental issues but have not been able to understand the effectiveness and potential of environmental graphic design in increasing public understanding and awareness of these issues. This research encourages the use of Environmental Graphic Design to convey messages about the environment intersecting with information design which is believed to provide new experiences and inspire behavior change in environmental issue and conservation efforts and encourage concrete actions in supporting environmental education.